Psychological Factors Influencing Organizational Commitment in Tech-Startups: A Systematic Mapping Study - Kireina Dewi Maghfiroh; Alia Naila Zahwa; Adellia Stephany (Jurnal Psikologi, 2026)
The technology industry is currently facing high volatility due to the Tech Winter phenomenon, which has triggered waves of mass layoffs and a significant increase in digital workloads, thereby threatening the stability of employee organizational commitment. This study aims to conduct a Systematic Mapping Study to synthesize literature from the 2021-2026 period regarding the psychological factors influencing this commitment. The methodology applied is a Systematic Literature Review (SLR) following the PRISMA protocol on 11 selected scholarly articles, analyzed through the lens of the Job Demands-Resources (JD-R) model.The results indicate a shift in management focus from transactional to relational-psychological approaches as an adaptive strategy to face the industrial crisis. Findings reveal that organizational commitment is predominantly influenced by organizational-level factors (63.6%), particularly through structural justice and systemic support. Meanwhile, individual-level factors (36.4%), such as self-leadership and personal resilience, serve as crucial prerequisites for the formation of emotional engagement. The JD-R analysis identifies that intense job demands are mitigated through a buffering mechanism of job and personal resources. This study concludes that talent stability can no longer be guaranteed solely through financial interventions, but rather through the strengthening of a mentally supportive and fair work ecosystem. The practical implication for startup management is the importance of integrating measurable mental well-being policies to build employee resilience. Future research is suggested to employ longitudinal studies to test the effectiveness of this mechanism across various stages of startup growth and explore the influence of local work culture.